Winter problems on mountain passes – Implications for cost-benefit analysis. (April 2015) - Bardal, Kjersti Granås; Mathisen, Terje Andreas
Highlights: Quantification of the impact of adverse weather on traffic speed. Methodology: structural equation modelling and classification and regression tree. Notable benefits for road users by reducing winter problems on mountain passes. CBA of infrastructure projects should include weather related benefits. Abstract: Cost-benefit analysis is a tool in government decision-making for determining the consequences of alternative uses of society's scarce resources. Such a systematic process of comparing benefits and costs was adopted in early years for transportation projects and it has been the subject of much refining over the years. There are still some flaws, however, in the application of the method. In this article we have studied the impact of weather conditions on traffic speed on low traffic roads often exposed to adverse weather. This is an issue not currently considered in the cost-benefit analysis of road projects. By using two analytical approaches—structural equation modelling and classification and regression tree analysis—the impact of the weather indicators temperature, wind speed, and precipitation on traffic speed has been quantified. The data relates to three winter months on the European Route 6 road over the mountain pass Saltfjellet in Norway. Increase in wind speed, increase in precipitation and temperatures around freezing point all caused significant decrease in traffic speed in the case studied. If actions were taken to reduce the impact of adverse weather on traffic (e.g. by building a tunnel through the mountain) this study indicates that the road users would gain a total benefit of approximately 2, 348, 000 NOK (282, 000 EUR) each winter at Saltfjellet if all the weather related benefits were included. We argue that this is a significant number that is highly relevant to include in CBAs. This applies both to the CBAs of new transportation projects as well as when resources are allocated for operation, maintenance, and monitoring of the existing transport systems. Including the weather related benefits would improve the application of CBA as a decision-making tool for policy makers.